Studies Of Alcohol Dehydrogenase And Aldehyde Dehydrogenase Activities During Acetic Acid Production By An Ethanol Resistant Immobilized Strain Of Saccharomyces Cerevisiae AB100 - MODHURIMA CHAKRABORTI; AJIT KUMAR BANIK (International Journal of Pharma and Bio Sciences, 2012)
The wine yeast Saccharomyces cerevisiae was immobilized in sodium alginate beads for production of acetic acid. In order to optimize immobilization conditions, a study was conducted using various concentrations of alginate, CaCl2 , cell loading, bead diameter etc. The optimized parameters were alginate concentration 4% (w/v), CaCl2 concentration 0.3 (M), cell: alginate ratio 5:4, storage period 24 hrs. and cell bead diameter of 3 mm. In comparison to free cells (1.0678 gm/100ml), the rate of fermentation by immobilized cell proved to be greater (1.395 gm/100ml), showing suitability for acetic acid production.